Analysis of the Impact of Digital Organizational Culture and Work Ethic on Member Performance with Organizational Commitment as an Intervening Variable (A Study at the Police Education and Training Institute) - Nana Supriatna; Osly Usman (Journal of Digital Business and Global Economy, 2026)
The effectiveness of resources is crucial for the success of public service in law enforcement agencies during digital transformation, this study explores how culture within organizations and employment ethic influence the effectiveness of personnel at the National Police Training and Education Center (Lemdiklat Polri), considering organizational commitment as a intervening factor, using an approach with descriptive and causal designs this study implements a survey technique with a Likert scale questionnaire. The research focuses on trainees in Lemdiklat Polri and Data analysis is conducted using Partial Least Squares Structural Equation Modeling (SEM-PLS) through SmartPLS software. The assessment of the model indicates an R-Square value of 47.9% for organizational commitment and 45.3% for employee performance with a strong combined Q-Square Predictive Relevance value of 71.5%. Hypothesis testing indicates that work ethic significantly influences organizational commitment and member performance. Organizational culture significantly affects organizational commitment. Nonetheless, organizational culture does not have a direct effect on individual performance. Commitment to the organization does not effectively mediate or moderate the influence of culture and the effect of work ethic on performance. Lemdiklat Polri staff, the findings emphasize that actual performance achievements of members are driven by individual motivational factors (work discipline) while organizational ethos and organizational dedication shape emotional comfort within the work environment. Leaders of Lemdiklat Polri should prioritize developing work indicators and transform formal work culture values to directly impact operational outputs in the field.